Exploring Cortical Thickness Alteration in Parkinson Disease Patients with Freezing of Gaits - E. Li; Xiuhang Ruan; Yuting Li; Guoqin Zhang; Mengyan Li; Xinhua Wei (Neural Plasticity)
Background: Freezing of gait (FoG) is a disabling gait disorder that commonly occurs in advanced stages of Parkinson’s disease (PD). The neuroanatomical mechanisms underlying FoG in PD are still unclear. The present study aims to explore alterations of structural gray matter (GM) in PD patients with FoG. Method: Twenty-four PD patients with FoG (FoG+), 37 PD patients without FoG (FoG-) and 24 healthy controls (HC) were included. All subjects underwent a standardized MRI protocol. The cortical thickness (CTh), segmentation volume without ventricles (BrainSegVolNotVent) and estimated total intracranial volume (eTIV) were analysed using the FreeSurfer pipeline. Results: CTh differences were found in the right middle temporal gyrus (rMTG) generally. Compared to that in HCs, the CTh of the rMTG in both the FoG+ and FoG- groups was smaller, while no significant difference between the FoG+ and FoG- groups. Correlation analyses demonstrated a negative correlation between the CTh of the rMTG and the UPDRS part II score in PD subjects, and a borderline significant correlation between the score of Freezing of Gait Questionnaire (FoGQ) and rMTG CTh. Additionally, receiver operating characteristic curve (ROC) analysis revealed a cut-off point of CTh =3.08 mm in the rMTG that could be used to differentiate PD patients and HCs (AUC =0.79, P <0.01). There were no differences in the BrainSegVolNotVent or eTIV among the 3 groups. Conclusions: Our findings currently suggest no significant difference between FoG+ and FoG- patients in terms of structural gray matter changes. However, decreased CTh in the rMTG related to semantic control may be used as a biomarker to differentiate PD patients and HCs.